Livelihoods, Household Income and Indigenous Technology in South Sumatra Wetlands - Elisa Wildayana; Dessy Adriani; M. Edi Armanto (Sriwijaya Journal of Environment, 2017)
he research aimed to analyze livelihoods, household income and indigenous technology in South Sumatra wetlands. The research method used field survey and interviews with respondents by using questionnaires. Respondents were determined with stratified random sampling method. The research data are classified into two parts, i.e. primary data and secondary data. The research showed that three main farmer’s groups settling in wetlands are spontaneous migration (Buginese and Banjarnese), new comers (transmigration) and indigenous people (local people from South Sumatra). All these tribes running the different farming systems, new comers and indigenous farmers implement farms with rice monoculture, while spontaneous migration applied multi commodities. The average land ownership of farm households is 1.95 ha which is intended for rice fields (0.94 ha), estate (0.85 ha), and livestock and fisheries (0.16 ha). Indigenous farmers have the minimum land (0.75 ha), however the spontaneous migration has the largest lands (3.10 ha). The larger the land ownership by farmers, thus the farmer’s income will increase if the land is cultivated by farmers. Household income structure of farmers is dominated by food crop farming and this has led to the vulnerability of farmer’s income due to the uncertainty of agricultural activities. The more varied sources of farmer’s income, the income of farmers will increase also. The learning process of spontaneous migration indicates that the farm should follow the nature, so the coercion of nature means to increase operational costs of farming.Keywords: Livelihoods, household, income, indigenous technology, wetlands